Heterogeneous Attitudes of Tourists toward Lionfish in the Mexican Caribbean: Implications for Invasive Species Management - Malpica-Cruz, Luis; Haider, Wolfgang; Smith, Nicola S.; Fernández-Lozada, Sergio; Côté, Isabelle M. (Frontiers in Marine Science, 2017)
Indo-Pacific lionfish (Pterois volitans and P. miles) are invasive predators established throughout the Wider Caribbean. They have already caused significant ecological impacts and have the potential to affect local economies that depend on coral reefs. Snorkeling and scuba diving are important activities that rely on aesthetically pleasant reefs. We asked whether lionfish-invaded reefs have lower aesthetic value and whether fees to help control the invasion might be acceptable to recreational divers and snorkelers in the Mexican Caribbean. To do so, we conducted a choice experiment in which tourists were asked to indicate their preferences for coral reef images with varying attributes that can be affected by lionfish. We specified a priori two classes of respondents, i.e. snorkelers and divers, but two latent classes of recreational divers (casual vs. committed) emerged on the basis of their preferences. Tourist age, commitment to snorkeling /diving, and lionfish awareness explained class membership. Casual divers and snorkelers preferred reefs with lionfish and accepted their impacts on the reefs. In contrast, committed divers disliked lionfish and associated impacts, and would elect to dive elsewhere if such impacts were high. Casual divers and snorkelers preferred options with low lionfish control fees, while committed divers were willing to pay high fees. Our results indicate potential economic impacts of the lionfish invasion in regions that depend on reef-related tourism, and that lionfish control fees might be acceptable to some but not all recreational users. However, because all tourists favored to a greater extent reef features that can be affected detrimentally by lionfish than they favored lionfish themselves, we predict that managing the lionfish invasion should be beneficial to the local reef tourism industry.